Iran's interests in Central Asia: A contemporary assessment - Efegil, Ertan; Stone, Leonard A. (My University, 2001)
Iranian policy towards Central Asia after 1991 was cautious, trying to thwart a US and Turkish breakthrough by maintaining close relations with Russia. But this Irano-Russian axis is at times under strain while Tehran and Washington are undertaking a cautious reassessment of their strained relationship. The reasons for these changes are complex. The Caspian Sea area is acquiring a new strategic dimension because of its developing potential for the production of hydrocarbons. The decrease of the Russian influence around the Caspian Sea is combined with a growing Western and specifically American penetration in the area. The weight of the American sanctions prevents Iran from taking its share of the new deal. The rapprochement between Iran and the conservative Arab States, coupled with Iran's renunciation of the exportation of revolution, has decreased the ideological antagonism with Washington. Iran is devising a more active and constructive policy. For Iran, the real strategic area is more the Caspian Sea than Central Asia strictly speaking. However, Iranian influence in this area is thwarted by the price Tehran is paying for its past mistakes in policy towards the Middle East. In no other direction does the isolation of Tehran put such an obstacle to an historical opportunity for Iran to become an overall regional power.
Keywords: foreign policy; hydrocarbon resource; international relations; policy analysis; Asia; Iran